Mechanical properties of natural fibre reinforced geopolymer composites: a review - Al-Ghazali, Noor Abbas; Abd. Aziz, Farah Nora Aznieta; Abdan, Khalina; Mohd. Nasir, Noor Azline (Universiti Putra Malaysia Press, 2022)
The cement production consumes many natural resources and energy, pollutes the environment, and cannot meet the current building materials’ green and sustainable development requirements. Therefore, geopolymers have gained popularity as cement replacements in recent years. Geopolymers have promising characteristics such as low energy consumption and carbon footprint, valuable compressive strength, fire resistance, flame resistance and good durability. However, these materials suffer from low tensile and flexural strength. Hence, fibres are added to overcome these issues and enhance their toughness index. Natural fibres are biodegradable, low-cost, renewable materials and widely available in many countries. This article reviewed previous Natural Fibre Reinforced Geopolymer Composites (NFRGC) studies, focusing on compressive strength, tensile and flexural strengths, and toughness. In addition, the available literature on the effect of the treatment methods of natural fibres on the mechanical properties of NFRGC has been addressed. The findings indicate that adding the appropriate type and content of natural fibres to geopolymer composites can enhance their mechanical properties. However, more attention should be paid to the effects of the pre-treatment of natural fibres on the performance of NFRGC.